Impact of Conflict Management Competence on Effective Management of Technical Education Programme in Tertiary Institutions in Southeast, Nigeria - Agbo, Nnaemeka Martin; Madonna Onwusuru, Ijeoma; Ihechiluru Miracle Okam; Mohammed Adamu Auta (Journal of Technical Education and Training, 2025)
The study explored the impact of conflict management competence on effective management of technical education programme in tertiary institutions in Anambra state. Specifically, the study determined the impact of arbitration, collective bargaining, dialogue and smoothing competencies on effective management of technical education programme in tertiary institutions in Anambra state. In this study, a mixed methods design was adopted because it involved collecting data to answer questions about the current state of the study subject through both the quantitative and qualitative means. The participants in in this study were 168 stakeholders in the management of technical education programme in tertiary institutions in South-Eastern Nigeria which offer technical education. Structured questionnaire and Interview were the instruments used for collecting data in this study. Cronbach’s Alpha was used to determine the reliability of the questionnaire. Reliability coefficients of 0.90, 0.92, 0.92 and 0.95 for arbitration, collective bargaining, dialogue and smoothing competencies respectively. Linear Regression and thematic analysis via illustrative quotes were used to analyze the data. Findings revealed that arbitration, collective bargaining, dialogue and smoothing competencies have a positive and significant impact on effective management of technical education programme in tertiary institutions in Anambra state.